2014
DOI: 10.1016/j.bbamcr.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Specific aquaporins facilitate Nox-produced hydrogen peroxide transport through plasma membrane in leukaemia cells

Abstract: In the last decade, the generation and the role of reactive oxygen species (ROS), particularly hydrogen peroxide, in cell signalling transduction pathways have been intensively studied, and it is now clear that an increase of ROS level affects cellular growth and proliferation pathways related to cancer development. Hydrogen peroxide (H2O2) has been long thought to permeate biological membranes by simple diffusion since recent evidence challenged this notion disclosing the role of aquaporin water channels (AQP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 44 publications
1
64
0
Order By: Relevance
“…Recently, members of the aquaporin protein family (AQP), initially described as bidirectional water transporters (1), have been found to channel also H 2 O 2 (7). We have recently shown that aquaporin-8 (AQP8) is essential to allow effective transport of H 2 O 2 across the plasma membrane, thus potentiating tyrosine phosphorylation induced by growth factors (6), a notion later corroborated by others (57). These data confirmed that H 2 O 2 acts as a rheostat of tyrosine kinase signaling and demonstrated that AQP8 guarantees efficient cytosolic import of H 2 O 2 likely produced by NOXes.…”
Section: Innovationmentioning
confidence: 49%
“…Recently, members of the aquaporin protein family (AQP), initially described as bidirectional water transporters (1), have been found to channel also H 2 O 2 (7). We have recently shown that aquaporin-8 (AQP8) is essential to allow effective transport of H 2 O 2 across the plasma membrane, thus potentiating tyrosine phosphorylation induced by growth factors (6), a notion later corroborated by others (57). These data confirmed that H 2 O 2 acts as a rheostat of tyrosine kinase signaling and demonstrated that AQP8 guarantees efficient cytosolic import of H 2 O 2 likely produced by NOXes.…”
Section: Innovationmentioning
confidence: 49%
“…This function was recently extended to NF-κB signaling in keratinocytes (32) or in response to environmental stresses in colonic epithelia (33). Similarly, AQP8 facilitates cellular accumulation of H 2 O 2 after VEGF stimulation, thereby enhancing PI3K activity and phosphorylation of MAPKs, two essential processes for leukemia cell proliferation (34). Combined with our previous work (11), the present study indicates that the contribution of AtPIP2;1 to guard cell responses to ABA and flg22 involves both a signaling and a hydraulic function.…”
Section: Discussionmentioning
confidence: 99%
“…This topological problem is solved by membrane-embedded aquaporin channels (AQPs). By serving as H 2 O 2 pores they facilitate the formation of local areas with an elevated H 2 O 2 concentration on both sides of the plasma membrane [13][14][15][16].…”
Section: Principles Of Reduction-oxidation Signalingmentioning
confidence: 99%